Development of Madura Batik MSME HR as a Catalyst for Green Entrepreneurship in Indonesia - Akh. Fawaid; Sudarmiatin Sudarmiatin; Wening Patmi Rahayu (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
The purpose of this study is to look at how human resource (HR) development in Batik Madura micro, small, and medium-sized enterprises (MSMEs) might act as a catalyst for green entrepreneurship in Indonesia. Green entrepreneurship is becoming the primary emphasis for decreasing negative environmental consequences while enhancing competitiveness in a global market that is more concerned with sustainability. HR plays a crucial role in implementing technical innovation and environmentally sustainable industrial processes. This study takes a qualitative method, with in-depth interviews with the owners, managers, and employees of MSME Batik Madura, as well as a literature analysis on green entrepreneurship.According to the study's findings, sustainable human resource development through training and education that emphasizes sustainability can boost productivity and efficiency in batik manufacturing. Furthermore, human resources with environmental consciousness and digital marketing abilities help Madurese batik products compete more effectively in national and international marketplaces. This study promotes collaboration among government, academics, and industry stakeholders to strengthen the development of human resources for Madura Batik MSMEs, which is the primary pillar in the transition to green entrepreneurship.